Highly effective catalytic peroxymonosulfate activation on N-doped mesoporous carbon for o-phenylphenol degradation. (April 2018) - Hou, Jifei; Yang, Shasha; Wan, Haiqin; Fu, Heyun; Qu, Xiaolei; Xu, Zhaoyi; Zheng, Shourong
Abstract: As a broad-spectrum preservative, toxic o -phenylphenol (OPP) was frequently detected in aquatic environments. In this study, N-doped mesoporous carbon was prepared by a hard template method using different nitrogen precursors and carbonization temperatures ( i.e., 700, 850 and 1000 °C), and was used to activate peroxymonosulfate (PMS) for OPP degradation. For comparison, mesoporous carbon (CMK-3) was also prepared. Characterization results showed that the N-doped mesoporous carbon samples prepared under different conditions were perfect replica of their template. In comparison with ethylenediamine (EDA) and dicyandiamide (DCDA) as the precursors, N-doped mesoporous carbon prepared using EDA and carbon tetrachloride as the precursors displayed a higher catalytic activity for OPP degradation. Increasing carbonization temperature of N-doped mesoporous carbon led to decreased N content and increased graphitic N content at the expense of pyridinic and pyrrolic N. Electron paramagnetic resonance (EPR) analysis showed that PMS activation on N-doped mesoporous carbon resulted in highly active species and singlet oxygen, and catalytic PMS activation for OPP degradation followed a combined radical and nonradical reaction mechanism. Increasing PMS concentration enhanced OPP degradation, while OPP degradation rate was independent on initial OPP concentration. Furthermore, the dependency of OPP degradation on PMS concentration followed the Langmuir-Hinshelwood model, reflecting that the activation of adsorbed PMS was the rate controlling step. Based on the analysis by time-of-flight mass spectrometry, the degradation pathway of OPP was proposed. Graphical abstract: Image 1 Highlights: N-doped mesoporous carbon catalysts were prepared for PMS activation. N-doped mesoporous carbon was highly active for OPP degradation. OPP degradation pathway was proposed.